Sām Dynasty between Legend and Reality - Maryam Musharraf (تاریخ ادبیات)
This article studies the roots of the dispute between the Sām dynasty and the central Kayanian government in Balkh (the old mythical reign of Persia). Although in Shahnameh, the Sām dynasty is presented as hostile to the Zoroastrian beliefs, and their opposition to Gushtāsp’s rule appears to be due to religious motives, the existence of political unrest in the Sistān region suggests that the conflict between the Sām family and the house of Gushtāsp is rooted in political issues, and the religious conflict is also a part of this political conflict. This means that if the demand for political independence and power had not been raised in the emirate of Sistān, religious differences could not have caused the marshaling of the two dynasties, whose conflict is reflected in significant parts of the national epic, especially in the story of Rostam and Esfandiyar.